The Influence Exerted by Time Frames on Consumers’ Willingness to Buy Nearly Expired Food - Song, Mingrui; Zhao, Yijun; Li, Xianguo; Meng, Lu (Frontiers in Psychology, 2021)
With the development of Internet e-commerce channels, online shopping platform has become the main channel for consumers to buy nearly expired food. Date label, as one of the main external clues, plays a decisive role in nearly expired food purchasing. Therefore, based on attention-related theory, this study attempts to explore the influence exerted by different time frames on consumers' willingness to buy and its mechanism. The results show that compared with date, consumers have higher willingness to buy nearly expired food when the expiration time is framed by delay. More specifically, compared to the date, the delay cause the individual to have a longer time perception, and thus more preference for nearly expired food. Meanwhile, the mediating effect of time perception is moderated by food type. The conclusion of this research is helpful to expand the theoretical framework of time frames and related fields on nearly expired food, as well as provide practical guidance for marketers to effectively promote nearly expired food.